Geach's Three Most Inspiring Errors Concerning Medieval Logic. (5th December 2014) - Klima, Gyula
Abstract: This paper analyses the import of three claims extracted from Geach's works concerning (i) theories of predication and the reference of common terms, (ii) the notions of being or existence, and (iii) the force/content distinction and theories of valid inference, respectively. The paper highlights the theoretical and historical errors involved in these claims as well as their enormous influence and inspiration in the field of the philosophical study of medieval logic and metaphysics.